1997
DOI: 10.1103/physrevlett.79.4830
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural Relaxation in AmorphousPd40Ni40P20: The Form

Abstract: Structural relaxation induced by hydrostatic pressure is experimentally observed for the metallic glass Pd 40 Ni 40 P 20 . The pressure dependence of the structural state is displayed in the shape of the glasstransition peak that is measured by means of differential scanning calorimetry after annealing treatments at 563 K and pressures up to 0.75 GPa. Quantification of the effect using the free-volume theory yields a formation volume of 5.9 6 0.5 Å 3 for defects in this glass. In combination with the previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…On the basis of our experiments, it might be true that phosphorus evaporation from the surface causes the monoclinic phase to become unstable so that it starts to decompose into phases 5 and 4 in the samples annealed in vacuum and Ar. Ruitenberg et al 31 observed pressure-induced structural relaxation in a Pd 40 Ni 40 P 20 ribbon glass. Structural relaxation might also affect the crystallization process of the glass.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our experiments, it might be true that phosphorus evaporation from the surface causes the monoclinic phase to become unstable so that it starts to decompose into phases 5 and 4 in the samples annealed in vacuum and Ar. Ruitenberg et al 31 observed pressure-induced structural relaxation in a Pd 40 Ni 40 P 20 ribbon glass. Structural relaxation might also affect the crystallization process of the glass.…”
Section: Resultsmentioning
confidence: 99%
“…From previous papers [16,17], we know that this procedure will bring the sample to an enthalpic state very close to a supercooled liquid, if it is observed on a long time scale. In other words, due to the long annealing procedure the sample relaxes into an enthalpic state that is equivalent to a state obtained after a long time scale cooling rate experiment.…”
mentioning
confidence: 99%
“…No crystallization of any kind was observed in any of the samples. Differential scanning calorimetry (DSC) was performed at ambient pressure in a DSC 7 (Perkin-Elmer) under constant heating rate using a small piece of the processed material.In several recent papers, it has been shown [16,17] that the relaxation state of glassy material can be monitored by the peak height of the heat flow at the glass transition during heating at a constant heating rate. The enthalpy recovery crossing from a nonergodic to an ergodic state indicates the amount of relaxation that has taken place at T g or below.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 For metallic systems, rare experimental data of T g vs pressure have been reported. Samwer et al 4 reported an increase of T g with pressure of 3.6 K/GPa for a Zr 46.8 Ti 8.2 Cu 7.5 Ni 10 Be 27.5 bulk metallic glass by an indirect enthalpy recovery method, 5 in which ambient-pressure differential scanning calorimetry ͑DSC͒ measurements of samples annealed under pressure were carried out. In this letter, we report a direct method, based on in situ hightemperature and high-pressure x-ray powder diffraction ͑XRD͒ measurements using synchrotron radiation, for studying the glass transition temperature under high pressure ͑above 1 GPa͒.…”
mentioning
confidence: 99%